EFFICIENCY AND COMPARISON OF TREATMENTS AGAINST GREEN MOLD IN ORANGES: a literature review - Santos, Leticia Souza; Moioli, Murilo Rafael; Manhani, Maria Raquel; Soares, Vanessa Aparecida (Revista Interface Tecnológica, 2022)
Brazil became the leader in the production of oranges around 1980 and 1990, standing out in the citrus area, increasing its exports over the decades, and proportionally expanding the global consumption demand of its various products. Considering the great importance of oranges for the Brazilian PIB,which generated more than 9 billion reais in 2020, their losses caused by the growth of molds must be studied and mitigated. This literature review describes the efficiency of chemical, physical and biological methods in controlling the proliferation of the fungus Penicillium digitatum, popularly known as green mold. The best methods were:  chemical compounds sodium bicarbonate and sodium carbonate with 100% effectiveness and the treatment with chitosan combined with hydrothermal treatment at 50°C which resulted in 92% control of the mold.
Keywords: Penicillium digitatum.; Fungus control in citrus; Orange post-harvest technology